Amiodarone Hepatotoxicity - Babatin, Mohamed; Lee, Samuel S.; Pollak, P. T. (Current Vascular Pharmacology, 2008)
Potential hepatotoxicity related to amiodarone therapy is often a concern when deciding whether to initiate or continue treatment with this medication. While mostly associated with long-term oral administration of the drug, toxicity has also been reported early during intravenous administration and months after discontinuation of therapy. In the majority of patients, it is discovered incidentally during routine testing of liver biochemistry and rarely do the hepatic effects develop into symptomatic liver injury or failure. Despite the widespread use of amiodarone, prospective clinical studies have been sparse and there has been little consensus among experts in the field regarding optimum monitoring for adverse effects in patients receiving this drug. In order to examine the current state of knowledge surrounding the incidence, pathogenesis and mechanism of liver effects associated with amiodarone, the existing literature was reviewed, with particular emphasis on clinical recommendations for monitoring.
Keywords: liver chemistry